Pengaruh Kas, Piutang dan Persediaan terhadap Likuiditas - Rivandi, Muhammad; Zunaifah, Lil Fatma (Jurnal Ekonomi Bisnis, Manajemen dan Akuntansi (Jebma), 2021)
The company when carrying out its business activities depends on the company’s capital or funds, if there is no capital or funds, the industry must try to find investors or third-party funds(DPK). The investor is any person or other entities that pledges funds with the intention of obtaining financial recovery, third party funds (DPK) are modes that come from the public or customer consisting of demand deposits, savings, and time deposits. Companies are expected to be careful when considering the company’s profits and losses because it can be a failure of the company to pay off debt and will be threatened with liquidity. Liquidity shows the company’s performance to pay off short-term financial responsibilities on time. The company’s liquidity is determined by the high current assets, namely assets that can be converted into cash which includes cash, marketable securities, receivables and inventories. This study aims to examine the effect of cash turnover, accounts receivable turnover, and inventory turnover. The sample of this research is 10 textile and garment companies listed on the Indonesia Stock Exchange (IDX) for the period 2014-2019 which were selected using the purposive sampling method. The data analysis method used in this study is a panel data regression model. Based on the results of hypothesis testing, that cash turnover has no effect on liquidity, accounts receivable turnover has no effect on liquidity, and inventory turnover has a significant negative effect on liquidity.